ANALYSIS OF COGNITIVE ABILITY AND DEPRESSION SCREENING AMONG ELDERLY PEOPLE AND ITS RELATIONSHIP WITH A HISTORY OF FALLS - Araujo, Danielle Taveira; Fernandes, Ana Julia Lemos; Lacerda, Ana Lara Pericole; Milazzo, Brendha Castro; Corrêa, Geovana Alves; Araujo, Maria Paula de Brito; Rodrigues, Fábio Fernandes; Fernandes, Viviane Lemos Silva (CIPEEX, 2025)
Aging is a continuous process of natural changes that often culminate in functional decline. Among the factors that can lead to a reduction in quality of life are falls. There are several risk factors that predispose the occurrence of these accidents, including reduced cognitive ability and depression, both of which can act as causes and consequences. Therefore, it is essential to assess these variables. In this sense, the Mine Mental State Examination (MEEM) and the Geriatric Depression Scale (EDG) were used to assess 120 elderly people from an Open University for the Elderly (UNIAPI), as well as to correlate their data with their history of falls in the last year. In the MEEM, the average overall score was 25 points. However, when checking the educational level of the elderly who reported a fall in the last year, it was found that the majority had incomplete high school education (41.7%) and achieved the expected score on the test, not indicating a depressive disorder. In the EDG, of those who suffered accidents due to falls, only 20% had a score equal to or greater than 6 points, which constitutes mild depression. Therefore, it is not possible to establish a direct relationship between cognitive ability and risk of depression with accidents due to falls.